Teaching languages—understanding cultures. A few remarks on feeling and experiencing in Hindi - Stasik, Danuta (Acta Orientalia Vilnensia, 2008)
University of Warsaw This article offers an overview of the expression of emotions in the Hindi language. First it discusses the Hindi word man, which in day-to-day communication denotes that something that is inside an individual, where one’s thoughts are born and thanks to which one can feel. Then, with reference to the opinion of Owen M. Lynch that in Hindi there is no specific equivalent of the verb to feel, the argument focuses on the analysis of a few examples of sentences in English, Hindi and Polish; all the English sentences feature the verb to feel, though not all of them refer to emotions/emotional states. The analysis reveals that in Hindi the equivalents of the verb to feel are less frequently used than in English (Polish stands somewhere in between). They appear especially in situations when one wants to share feelings that have been experienced with others. Also of great importance is that in Hindi in the majority of the sentences analysed the so-called experiencer subjects, or dative experiencer subjects, are used.